MENCEGAH DAN MEMBERANTAS KORUPSI DIMULAI DARI DIRI SENDIRI - Samuel Pardamean Sijabat; Zahra Maharani; Devika Dwi Nursaputri (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
The general impact of corruption in Indonesia, which encompasses economic aspects and the decline of public trust, requires a comprehensive solution that goes beyond formal law enforcement. Public participation through the internalization of integrity values, instilled from an early age, is key. Therefore, we must explore how the principles of honesty and individual responsibility serve as a bulwark against a corrupt mentality. Using a literature review, it was found that character building must be carried out through concrete daily actions, such as being disciplined and rejecting deviant behavior, as crucial steps in establishing a safe and corruption- free social ecosystem. This personal awareness is seen as a driver of better social transformation and integrity in the future.